The Role of Compensation in Improving Employee Performance - Kosasih Kosasih; Lie Anto; Antonius Kurniawan; Ageng Prasetia; Erniaty Beddu (Annals of Human Resource Management Research, 2026)
Purpose: This study aims to empirically examine the effects of work environment, work experience, and education level on employee performance, as well as to analyze the mediating role of compensation in Indonesian State-Owned Enterprises (SOEs). Research Methodology: A quantitative approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS) was employed, with a sample of 110 employees working in SOEs, each with at least five years of work experience. Data were collected using a structured questionnaire on a 5-point Likert scale. Results: The study found that the work environment, work experience, and education level significantly impacted employee performance. However, compensation did not directly affect the performance. Compensation only mediated the relationship between work experience and performance, not between the work environment and education level. Conclusions: The work environment, work experience, and education level significantly affect employee performance in SOEs. Compensation was found to mediate the relationship between work experience and performance, but not for the work environment or education level. These results suggest that a conducive work environment, relevant work experience, and education can enhance performance. Compensation can serve as an additional motivator for high-performing employees to engage in CWB. Limitations: This study is limited to employees in State-Owned Enterprises and uses a cross-sectional design, which may restrict the generalizability of the findings. Future research should include other sectors and additional variables. Contributions: This study contributes to the HRM literature by clarifying the inconsistent role of compensation and highlighting the importance of experiential and environmental factors in enhancing employee performance.